スカンジナビア半島北部におけるMF/HF帯電波の観測計画 - 佐藤, 由佳; Yuka, Sato (2017)
第8回極域科学シンポジウム/個別セッション：[OS] 宙空圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OS] Space and upper-atmosphere sciences Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object